Raccontare un virus selvaggio: Covid-19, New Wild e realismo multispecie - Pinto, Isabella (B@belonline, 2021)
At the crossroads between the storytelling philosophy, philosophy of science and anthropology, the challenge of this article is to elaborate new critic and creative tools, useful in the face of the emergence of the wild virus COVID-19, a global phenomenon that we can inscribe within the feral ecologies, that are connected to the Anthropocene, the Capitalocene, and the Plantationocene, and showing the presence of the new wild, concept proposed by Anna L. Tsing. To map this phenomenon, the article analyzes the tools of multispecies anthropology, and by relating them with some innovative narrative practices that imaging otherwise the Freud’s unheimlich. Connected also with the Donna Haraway’s work, the ‘Multispecies Realism’ is outlined, a toolbox necessary to tell the entanglements between the stories of the catastrophe and the stories of the Chthulucene, such as demonstrates the multispecies stories of the toxic alien alga, Planktothrix Rubescens, recently appeared in Lake Vico and Lake Bolsena (Italy).